On the fast fluid dynamics and fractional step methods to predict the coupled indoor temperature and velocity fields. (1st February 2023) - Zhou, Pengzhi; Wang, Haidong; Dai, Yuwei; Xue, Yu; Huang, Chen
Abstract: The two-way coupling of temperature and flow fields in the indoor environment makes the conventional CFD simulation computationally intensive, especially when the transient evolution of temperature and velocity fields is of interest in areas such as unsteady ventilation. This study, by applying different splitting CFD methods (fast fluid dynamics (FFD) and fractional step (FS) method) to solve the momentum equation to decouple velocity and pressure fields, further explored different strategies to tackle the coupled temperature equation, and validated the different sequences of operation based on different combinations of temperature/velocity solution schemes. Each operational sequence of different combined numerical schemes was validated on a mixed convection airflow benchmark case with a heated floor. The results showed that different operational sequences using the numerical schemes which considered the strong coupling effect of temperature and flow fields could predict the final steady-state result well, while for the transient simulation that need to track the physical flow/thermal fields variation process precisely, the operational sequence which introduce the effect of buoyancy into volumetric flux to solve pressure Poisson equation showed better accuracy and owned the capability of predicting the same transient evolution process as conventional CFD method. Based on the comprehensive comparison, several promising numerical schemes under proper operational sequence were recommended and the highest computing efficiency was provided by sequence D of RIPC + Iterative which saved 68% computing time compared to the conventional CFD method. Highlights: Decoupling temperature and flow fields by FFD and FS methods in OpenFOAM. Both final steady-state and transient results are validated and analyzed. FS method without SL for convection term performs more accurate than FFD method. The operational sequence is important to the accuracy and speed of numerical scheme. Sequence D of RIPC + Iterative scheme saves as much as 68% computing time for transient simulation.